Action Research : Pemberdayaan Bystander untuk Mencegah Perundungan di Sekolah Melalui Program Pelatihan Keterampilan Empati - Cynthia Halim; Ratna Djuwita (Jurnal Perkotaan, 2018)
Bullying in a form of intimidation that junior peers receive from their seniors are still happening in several high schools in Jakarta area, namely XYZ High School. The immediate effect of intimidation include fear of being near any place in that specific school that is considered as the senior turf. This in turn affects negatively on the students' sense of security and feeling of peace, thus possesses threats on their academic as well as non-academic achievements. This research aims to empower students to become bystanders who are willing to intervene thus prevent the occurrence of bullying. The students' willingness to be able to intervene requires certain skills in empathy, thus this intervention program provides training to increase empathy aimed at a group of student council members in order for them to be able to intervene properly. Literatures in empathetical skills used in the design of this program will increase prosocial behaviour so that bullying will decrease on its own after its delivery. The program includes: recognizing others' perspectives, recognizing others' needs, and increasing the sense within self to help others in need. This research used an action research design that focuses on explorative narratives. Analysis used a Wilcoxon signed-ranks that showed students' empathetical skills increased after intervention of program was delivered (pretest-post test score on empathetical skills IRI Z = 2,836, p <0,005). The increased empathetical skills in students are expected to decrease bullying behaviour within XYZ High School in Jakarta.